Cholesterol Contributes to Diabetic Nephropathy through SCAP-SREBP-2 Pathway - Hong Sun; Yang Yuan; Zi-Lin Sun (International Journal of Endocrinology)
Diabetic nephropathy (DN) has been associated with the presence of lipid deposition. We hypothesized that the disruption of intracellular cholesterol feedback may contribute to DN. Diabetes was induced by high fat/sucrose diet and low-dose intraperitoneal injection of streptozocin (STZ) in male Sprague-Dawley rats. Then diabetic rats were randomly divided into two groups: untreated diabetic group (DM) and atorvastatin-treated group (DM + AT). We found that the levels of serum blood urea nitrogen and creatinine, as well as 24-hour urine protein and urinary neutrophil gelatinase-associated lipocalin, were significantly increased in diabetic rats. This result indicated that the diabetic rats suffered from functional renal damage. We also observed lipid droplet accumulation and increase in 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoAR), low density lipoprotein receptor (LDLr), sterol regulatory element binding protein-2 (SREBP-2), and SREBP-cleavage activating protein (SCAP) in the kidneys of diabetic rats. However, atorvastatin ameliorated renal lipid accumulation and improved the renal function of diabetic rats despite an increase in mRNA and protein expressions of HMG-CoAR, LDLr, and SREBP-2. These results demonstrated that intracellular cholesterol feedback regulation is disrupted in rats with type 2 diabetes, thereby causing renal cholesterol accumulation. Atorvastatin ameliorated renal cholesterol accumulation by reducing renal cholesterol synthesis.